GAMBARAN EPIDEMIOLOGI PENYAKIT TUBERKULOSIS PARU DI POLIKLINIK PARU RSUD Dr. H. CHASAN BOESOIRIE TERNATE TAHUN 2018 - amina amina; dwi handoko; dewi darmayanti (Fakultas Kedokteran, Universitas Khairun, 2020)
ABSTRACTTuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis, an bacillus-acid resistant that is transmitted through the air. TB is an main global healt problem and it’s one of the 10 leading causes of death in the world. Epidemiologically, the distribution of TB attacks more in the productive age, but all age groups are at risk of TB. This study aims to determine the epidemiological picture of pulmonary tuberculosis in RSUD Dr. H. Chasan Boesoeri Ternate in 2018. The design in this study was retrospective descriptive. The study was conducted in the pulmonary clinic. Sampling with a total sampling technique. The type of data uses medical record data then the data was analyzed descriptively. Based on the results of this study that the distribution of pulmonary TB aged 25-34 years more affected by pulmonary TB as many as 35 patients (29.9%), based on male sex more affected by pulmonary TB as many as 73 patients (62.4%) , the history of treatment of pulmonary TB patients more who came for treatment were 115 new cases (98.3%), new laboratory test results showed negative pulmonary TB patients 60.7%, the anatomical location of TB more in the lungs as many as 91 patients (77 , 8%) and based on the residential address of more pulmonary TB patients were located in Ternate Selatan District 47%. The conclusion from the results of this study is that pulmonary TB patients who come for treatment are more aged 25-34 years, male sex, with new cases are higher, TCM results are more negative, anatomic location in the lungs and more patient addresses in Ternate. Keywords : epidemiology, RSUD, TB pulmonary